TNF-alpha increases the intrinsic excitability of cerebellar Purkinje cells through elevating glutamate release in Bergmann Glia - Shim, Hyun Geun; Jang, Sung-Soo; Kim, Seung Ha; Hwang, Eun Mi; Min, Joo Ok; Kim, Hye Yun; Kim, Yoo Sung; Ryu, Changhyeon; Chung, Geehoon; Kim, YoungSoo; Yoon, Bo-Eun; Kim, Sang Jeong (Nature Publishing Group, 2018)
For decades, the glial function has been highlighted not only as the 'structural glue', but also as an 'active participant' in neural circuits. Here, we suggest that tumor necrosis factor alpha (TNF-alpha), a key inflammatory cytokine, alters the neural activity of the cerebellar Purkinje cells (PCs) by facilitating gliotransmission in the juvenile male rat cerebellum. A bath application of TNF-alpha (100 ng/ml) in acute cerebellar slices elevates spiking activity of PCs with no alterations in the regularity of PC firings. Interestingly, the effect of TNF-alpha on the intrinsic excitability of PCs was abolished under a condition in which the type1 TNF receptor (TNFR1) in Bergmann glia (BG) was genetically suppressed by viral delivery of an adeno-associated virus (AAV) containing TNFR1-shRNA. In addition, we measured the concentration of glutamate derived from dissociated cerebellar cortical astrocyte cultures treated with TNF-alpha and observed a progressive increase of glutamate in a time-dependent manner. We hypothesised that TNF-alpha-induced elevation of glutamate from BGs enveloping the synaptic cleft may directly activate metabotropic glutamate receptor1 (mGluR1). Pharmacological inhibition of mGluR1, indeed, prevented the TNF-alpha-mediated elevation of the intrinsic excitability in PCs. Taken together, our study reveals that TNF-alpha triggers glutamate release in BG, thereby increasing the intrinsic excitability of cerebellar PCs in a mGluR1-dependent manner.